The changing water cycle: hydroclimatic extremes in the British Isles. (30th June 2016) - Burt, T.P.; Howden, N.J.K.; Worrall, F.
Abstract : This focus article is concerned with long‐term changes in hydroclimatic extremes across the British Isles. The combination of short records, poor data quality, nonstationarity, and other methodological constraints is a major obstacle to the attribution of change. Given the interaction of drivers, notably hydroclimate and land use, linking cause and effect can be difficult, especially where records are short. This focus article emphasizes the particular value of long hydrological records in seeking to understand the scale of change currently affecting British and Irish river basins. Homogeneous records of precipitation and river flow are used to explore long‐term changes and to establish linkage with large‐scale atmospheric drivers. Using very long records allows subtle, underlying trends to be detected within noisy records; since most records of river flow are only a few decades long, very long precipitation records are used to provide a context and evidence of century‐scale monotonic trends. Analysis of flow extremes in the British Isles shows a clear linkage with indices of large‐scale atmospheric circulation; relatively simply indices of weather type and atmospheric circulation provide a good level of explanation. At the longest timescales, there has been important variation in precipitation: a monotonic increase in winter, not seen in summer where interdecadal variability is the dominant pattern. With one exception, significant trends in summer are negative, including in the uplands; this unexpected result deserves further consideration across the British Isles. WIREs Water 2016, 3:854–870. doi: 10.1002/wat2.1169 This article is categorized under: Science of Water > Water and Environmental Change Science of Water > Water Extremes Abstract :